One ligand fits all: lanthanide and actinide sandwich complexes comprising the 1, 4-bis(trimethylsilyl)cyclooctatetraenyl (=COT′′) ligand12. (16th June 2015) - Rausch, Janek; Apostolidis, Christos; Walter, Olaf; Lorenz, Volker; Hrib, Cristian G.; Hilfert, Liane; Kühling, Marcel; Busse, Sabine; Edelmann, Frank T.
Abstract : Twelve new lanthanide and actinide sandwich complexes containing the 1, 4-bis(trimethylsilyl)cyclooctatetraenyl ligand (COT′′) have been prepared and structurally characterized by X-ray diffraction. Abstract : The series of anionic lanthanide(iii ) sandwich complexes of the type [Ln(COT′′)2 ] − (COT′′ = 1, 4-bis(trimethylsilyl)cyclooctatetraenyl dianion) has been largely extended by the synthesis of eight new derivatives ranging from lanthanum to lutetium. The new compounds [Li(DME)3 ][Ln(COT′′)2 ] (Ln = Y (1 ), La (2 ), Pr (3 ), Gd (4 ), Tm (6 ), Lu (8 )) and [Li(THF)4 ][Ln(COT′′)2 ] (Ln = Ho (5 ), Tm (7 )) were prepared in good yields following a straightforward synthetic protocol which involves the treatment of LnCl3 with 2 equiv. of in situ -prepared Li2 COT′′ in either DME (=1, 2-dimethoxyethane) or THF. The neutral actinide sandwich complexes An(COT′′)2 (An = Th (9 ), U (10 )) and An(COT′′′)2 (COT′′′ = 1, 3, 6-tris(trimethylsilyl)cyclooctatetraenyl dianion; An = Th (11 ), U (12 )) were synthesized in a similar manner, starting from ThCl4 or UCl4, respectively. The COT′′ ligand imparts excellent solubility even in low-polar solvents as well as excellent crystallinity to all new compounds studied. All twelve new f-element sandwich complexes have been structurally authenticated by single-crystal X-ray diffraction. All are nearly perfect sandwich complexes with little deviation from the coplanar arrangement of the substituted COT′′ rings. Surprisingly, all six [Li(DME)3 ][Ln(COT′′)2 ] complexes covering the entire range of Ln 3+ ionic radii from La 3+ to Lu 3+ are isostructural (space group P 1̄). Compound10 is the first uranocene derivative for which 13 C NMR data are reported.